2018
DOI: 10.1177/0361198118799033
|View full text |Cite
|
Sign up to set email alerts
|

Developing Assessment Criteria for Sustainable Transport Appraisal

Abstract: Defining a clear, comprehensive, and non-overlapping set of assessment criteria is a crucial step in multi-criteria analysis processes. Although criteria are typically developed based on planning objectives, there currently exists no standard procedure for conducting this exercise when both transportation and wider sustainable development goals need to be considered jointly. Based on research applying the multi-actor multi-criteria analysis approach to the case of a high-speed rail project in the UK, this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…The criteria weighting process described below (Sections 3.4.1 and 3.4.2) is based on a list of assessment criteria developed by Barradale and Cornet [23] in a prior, preparatory stage of this research. Using the criteria listed in the Transport Analysis Guidance (WebTAG) by the UK government [29] and the impacts assessed in the HS2 appraisal documents [32,38] as a starting point, Barradale and Cornet [23] consulted a wide range of experts, adopting an iterative, mixed deductive/inductive approach to produce a comprehensive and coherent list of criteria for comparing HS2 and its alternatives. In addition to direct project impacts (those costs and benefits typically considered in transport appraisal, including the official appraisal of HS2 Phase I), this list includes broader impacts on society and the environment.…”
Section: Assessmentmentioning
confidence: 99%
See 3 more Smart Citations
“…The criteria weighting process described below (Sections 3.4.1 and 3.4.2) is based on a list of assessment criteria developed by Barradale and Cornet [23] in a prior, preparatory stage of this research. Using the criteria listed in the Transport Analysis Guidance (WebTAG) by the UK government [29] and the impacts assessed in the HS2 appraisal documents [32,38] as a starting point, Barradale and Cornet [23] consulted a wide range of experts, adopting an iterative, mixed deductive/inductive approach to produce a comprehensive and coherent list of criteria for comparing HS2 and its alternatives. In addition to direct project impacts (those costs and benefits typically considered in transport appraisal, including the official appraisal of HS2 Phase I), this list includes broader impacts on society and the environment.…”
Section: Assessmentmentioning
confidence: 99%
“…Respondents were also given the possibility of adding openended comments. This qualitative data was used in earlier stages of the research to refine the criteria list (see [23]).…”
Section: Response Elicitationmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, using three selected appraisal criteria which refer to three dimensions of sustainability, Mahmoudi et al (2019) presented an integrated tool combining the game theory and the "data envelopment analysis (DEA)" for sustainable road network project. Barradale and Cornet (2018) applied the multi-actor multi-criteria assessment tool to describe the transport evaluation criteria involving direct project impacts, indirect societal and environmental impacts for "sustainable transport appraisal of rail projects (STARPs)". Muvawala et al (2020) observed the impact of "road transport infrastructure investment (RTII)" on Uganda's economic performance and measured the economic aspects related with disorganized urban road transport infrastructure structure in Uganda.…”
Section: Introductionmentioning
confidence: 99%